Reelin Signals through Apolipoprotein E Receptor 2 and Cdc42 to Increase Growth Cone Motility and Filopodia Formation - Leemhuis, Jost (Society for Neuroscience, 2010)
Lipoprotein receptor signaling regulates the positioning and differentiation of postmitotic neurons during development and modulates neuronal plasticity in the mature brain. Depending on the contextual situation, the lipoprotein receptor ligand Reelin can have opposing effects on cortical neurons. We show that Reelin increases growth cone motility and filopodia formation, and identify the underlying signaling cascade. Reelin activates the Rho GTPase Cdc42, known for its role in neuronal morphogenesis and directed migration, in an apolipoprotein E receptor 2-, Disabled-1-, and phosphatidylinositol 3-kinase-dependent manner. We demonstrate that neuronal vesicle trafficking, a Cdc42-controlled process, is increased after Reelin treatment and further provide evidence that the peptidergic VIP/PACAP38 system and Reelin can functionally interact to promote axonal branching. In conclusion, Reelin-induced activation of Cdc42 contributes to the regulation of the cytoskeleton of individual responsive neurons and converges with other signaling cascades to orchestrate Rho GTPase activity and promote neuronal development. Our data link the observation that defects in Rho GTPases and Reelin signaling are responsible for developmental defects leading to neurological and psychiatric disorders.